2023
DOI: 10.1111/1751-2980.13192
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive analysis of partial peristalsis recovery after peroral endoscopic myotomy in patients with achalasia

Abstract: Objective: To determine whether peroral endoscopic myotomy (POEM) improves esophageal peristalsis and to investigate the association between recovery of esophageal peristalsis after POEM and clinical features of the patients. Methods: In this single-center retrospective study, data were collected from medical records of the patients with achalasia who underwent POEM between January 2014 and May 2016. Demographics data, high-resolution esophageal manometry parameters, Eckardt score, and gastroesophageal reflux … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…A retrospective study involving 237 patients noted partial peristaltic recovery in 22% of patients after POEM[ 35 ]. Another study indicated a lower frequency of GERD symptoms and reflux esophagitis in patients exhibiting partial peristaltic recovery post-POEM, with preprocedural LES resting pressure and the Eckardt score predictive of this recovery[ 36 ]. However, these findings require confirmation through high-quality clinical trials.…”
Section: Prevention Of Gerd After Poemmentioning
confidence: 99%
“…A retrospective study involving 237 patients noted partial peristaltic recovery in 22% of patients after POEM[ 35 ]. Another study indicated a lower frequency of GERD symptoms and reflux esophagitis in patients exhibiting partial peristaltic recovery post-POEM, with preprocedural LES resting pressure and the Eckardt score predictive of this recovery[ 36 ]. However, these findings require confirmation through high-quality clinical trials.…”
Section: Prevention Of Gerd After Poemmentioning
confidence: 99%